Світлопросторова композиція сакральних будівель Ле Корбюзьє - Яців, Мирослав; Яців, Софія; Yatsiv, Myroslav; Yatsiv, Sofiia (Видавництво Львівської політехніки, 2023)
Статтю присвячено аналізу світлової композиції в просторі сакральних будівель спроектованих видатним французьким архітектором Ле Корбюзьє в 50-60-х роках минулого століття. Розкрито сутність методики проектування світлового середовища модерних храмів архітектора, встановлено способи та засоби формування світло-просторових композицій цих будівель. Виявлено напрямки, характер та особливості поширення природного світла у внутрішньому просторі храмів та їхнє значення у формуванні світлоколірного середовища і сакральної атмосфери, що занурює прихожан у стан зосередженості й "тиші", необхідних для роздумів і спільної молитви.

The article discusses the ways, methods and means used by architect Le Corbusier to organize the light environment in his sacred buildings: the chapel of Notre Dame du Haut in Roncham; the church of the Dominican monastery complex Notre Dame de la Tourette; the Catholic church of Saint-Pierre-de-Firmin. The churches were built in France in the 50s and 70s of the last century, with the exception of the church in Firmin, which was completed in 2006. In these sacred buildings, built in the modernist style, the architect abandons the traditional architectonics of sacred buildings of the past and declares the renewal of artistic principles, the novelty of architectural forms and structures. The architecture of the churches, which speaks the language of pure form, found in precise proportions, reveals Le Corbusier's characteristic fusion of architecture and the plastic arts, their interdependence and mutual enrichment. By shaping the light-spatial composition of the interior of these churches, the architect tried to achieve an atmosphere of concentration and "silence" so necessary for contemplation, reflection, and common prayer. To create this atmosphere, Le Corbusier chose the twilight that prevailed in the interior of his churches, the austere and dry aesthetics of the wall surfaces, which compared to churches built in the Romanesque period. It was important for him to have a very refined, dosed natural light entering the sacred space of the buildings. He achieves this effect using different methods in each of his sacred projects. By controlling the amount of light, through a combination of direct, reflected and diffused natural light entering through skylights, the architect creates a changing light-spatial composition that differs from the light environment of traditional churches. According to the architect, the skylights, selectively and carefully placed in the spatial structure of the churches, should create an atmosphere of mysticism and focus the attention of the parishioners on prayer. The requirements of religion had little influence on the architect's plan. The shape of the temples and the light and space composition of the interior space were a response to the psychophysiology of the senses. The choice of an ascetic interior for his buildings, without any decoration, leaves room for the changing natural light that illuminates the magical, mystical, indescribable space, and is perhaps the only symbol of its sacredness.
Light and space composition of Le Corbusier’s sacred buildings
Keywords: природне світло; сакральний простір; сакральна архітектура; храм; композиція; модернізм; natural light; sacred space; sacred architecture; temple; composition; modernism; 72.01; 726